JM-20, a novel hybrid molecule, protects against rotenone-induced neurotoxicity in experimental model of Parkinson's disease. (18th January 2019) - Fonseca-Fonseca, Luis Arturo; Wong-Guerra, Maylin; Ramírez-Sánchez, Jeney; Montano-Peguero, Yanay; Padrón Yaquis, Alejandro Saúl; Rodríguez, Abel Mondelo; da Silva, Víctor Diógenes Amaral; Costa, Silvia Lima; Pardo-Andreu, Gilberto L.; Núñez-Figueredo, Yanier
Highlights: Novel hybrid molecule (JM-20) prevents rotenone-induced cell death. JM-20 reduced oxidative stress and improved mitochondrial functions in rotenone-treated rats. JM-20 prevents the increase in sensory indifference (apathy) in rats chronically treated with rotenone. JM-20 increased survival and body weight gain of animals treated with rotenone. Abstract: Oxidative stress and mitochondrial dysfunction are two pathophysiological factors often associated with the neurodegenerative process involved in Parkinson's disease (PD). The aim of this study was to investigate the effects of a novel hybrid molecule, named JM-20, in different in vitro and in vivo models of PD induced by rotenone. To perform in vitro studies, SHSY-5Y cells were exposed to rotenone and/or treated with JM-20. To perform in vivo studies male Wistar rats were intoxicated with rotenone (2.5 mg/kg) via intraperitoneal injection and/or treated with JM-20 (40 mg/kg) administered via oral (for 25 days, both treatment). Rats were evaluated for global motor activity by measurement of locomotor activity. In addition, the effects on mortality, general behavior and redox parameters were also investigated. JM-20 protected SHSY-5Y cells against rotenone-induced cytotoxicity, evidenced by a significant diminution of cell death. In in vivo studies, JM-20 prevented rotenone-induced vertical exploration and locomotion frequency reductions, moreover prevented body weight loss and mortality induced by rotenone. It also improved the redox state of rotenone-exposured animals by increasing superoxide dismutase and catalase activities, total tissue-SH levels and decreasing malondialdehyde concentrations. Finally, JM-20 inhibited spontaneous mitochondrial swelling and membrane potential dissipation in isolated rats brain mitochondria. These results demonstrate that JM-20 is a potential neuroprotective agent against rotenone-induced damage in both in vitro and in vivo models, resulting in reduced neuronal oxidative injury and protection of mitochondria from impairment.